Congenital neurodevelopmental anomalies in pediatric and young adult cancer. Issue 10 (29th August 2017) - Wong‐Siegel, Jeannette R.; Johnson, Kimberly J.; Gettinger, Katie; Cousins, Nicole; McAmis, Nicole; Zamarione, Ashley; Druley, Todd E.
Abstract : Congenital anomalies that are diagnosed in at least 120, 000 US infants every year are the leading cause of infant death and contribute to disability and pediatric hospitalizations. Several large‐scale epidemiologic studies have provided substantial evidence of an association between congenital anomalies and cancer risk in children, suggesting potential underlying cancer‐predisposing conditions and the involvement of developmental genetic pathways. Electronic medical records from 1, 107 pediatric, adolescent, and young adult oncology patients were reviewed. The observed number (O) of congenital anomalies among children with a specific pediatric cancer subtype was compared to the expected number (E) of anomalies based on the frequency of congenital anomalies in the entire study population. The O/E ratios were tested for significance using Fisher's exact test. The Kaplan–Meier method was used to compare overall and neurological malignancy survival rates following tumor diagnosis. Thirteen percent of patients had a congenital anomaly diagnosis prior to their cancer diagnosis. When stratified by congenital anomaly subtype, there was an excess of neurological anomalies among children with central nervous system tumors (O/E = 1.56, 95%CI 1.13–2.09). Male pediatric cancer patients were more likely than females to have a congenital anomaly, particularly those <5 years of age (O/E 1.35, 95%CI 0.97–1.82). Our study provides additional insight into the association between specific congenital anomaly types and pediatric cancer development. Moreover, it may help to inform the development of new screening policies and support hypothesis‐driven research investigating mechanisms underlying tumor predisposition in children with congenital anomalies.